DEVELOPMENT AND DESIGN OF AN AUTOMATIC FABRIC CUTTING MACHINE INDUSTRY FOR THE TEXTILE - Galang Rimba Nusantara; Agung Albaru Albaru; Chandly Tambunan Tambunan; Fardin Hasibuan Hasibuan (Universitas Riau Kepulauan, 2025)
This study aims to develop an economical, efficient, and precise automatic fabric cutting machine to improve productivity and quality in small to medium-scale textile industries. Traditional manual cutting methods often lead to inconsistent results, lengthy cutting times, and human error, which can hinder production efficiency. The research involves designing the machine, selecting key components, assembling the tool, and testing its performance on various fabric types. Results show that the automatic fabric cutting machine enhances cutting speed by up to 50% with consistent precision, while also reducing fabric waste caused by cutting errors. The study concludes that this machine offers a viable solution for textile industries to improve efficiency and quality at a lower cost compared to commercial machines. Further improvements are suggested to include automated pattern-cutting capabilities and better fabric compatibility.